Integration of Islamic Values in Anti-Corruption (A Secondary Data Study on Public Perception of Corruption and Religion) - Trisnawati; Akhmad Hasan Saleh (Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2024)
This study examines the acceptance of Indonesia society towards the integration of Islamic values in corruption eradication policies. Through secondary data in the form of research survey data, this paper aims to explore the public's knowledge about Islamic values related to anti-corruption, their views on the effectiveness of Islamic values-based policies, and the level of support for the integration of these values in public policy. The survey results showed that the majority of respondents had a fairly good knowledge of relevant Islamic values, such as honesty (ash-shidq), justice (al-adl), and amanah. Most respondents believe that anti-corruption policies based on Islamic values will be more effective, with high support for the integration of these values. However, there are concerns regarding the consistency of implementation and the potential for politicization of religious values. This research suggests improving education and socialization of Islamic values, consistency in policy implementation, and collaboration with religious institutions as strategic steps to strengthen the eradication of corruption in Indonesia.